Role of Mitophagy in Coronary Heart Disease: Targeting the Mitochondrial Dysfunction and Inflammatory Regulation - Liu, Mingxuan; Wu, Ying (Frontiers in Cardiovascular Medicine, 2022)
Coronary heart disease (CHD) has always been considered as the main cause of death worldwide. In the past few decades, the medical community has conducted in-depth excavation and research on the pathological mechanism and effective treatment methods of coronary heart disease. At present, a variety of therapeutic drugs and treatment technologies have greatly reduced the burden on global public health. However, the severe arrhythmia and myocardial fibrosis (or myocardial hypertrophy) accompanying coronary heart disease in the later stage are medical problems that need to be solved urgently. Mitochondria, as an organelle covered by two membranes in cardiomyocytes, are an important structural component for energy production in cells, and they are also the main place for cells to perform aerobic respiration. Mitochondria are involved in arrhythmia, myocardial fibrosis, and acute coronary heart disease. Both myocardial ischemia/hypoxia injury can play an important regulatory role. Mitochondrial dysfunction or mitophagy disorders (including receptor-dependent mitochondrial autophagy and receptor-independent mitochondrial autophagy) have been considered to be an important part of the pathogenesis of coronary heart disease, especially mitochondrial autophagy. Mitophagy is a selective autophagy, which refers to the process of using autophagy to eliminate mitochondria with abnormal functions in the cell. As organelles that participate in and regulate inflammation, mitochondria can exist as a "mediator" in the inflammatory damage of cardiomyocytes or vascular endothelial cells, and mitochondrial autophagy can clear mitochondria or organelles damaged by inflammation under normal conditions. We reviewed the important experimental evidence that mitochondrial homeostasis or mitochondrial quality control is involved in the pathological mechanism of coronary heart disease. At the same time, I summarized and reviewed relevant regulatory drugs that target mitochondrial function and quality control.